Policy Implementation of Marriage Age Maturity Program to Achieving a Population Control and Family Development - Nurani Ajeng Tri Utami; Ulil Afwa (Universitas Kuningan, 2020)
Marriage Age Maturity, PUP is a BKKBN program which regulates the age maturity limit for marriage, a minimum of 20 years for women and a minimum of of 25 years for men. This provision differs from the minimum marriageable age stated in the marriage act. The importance of PUP program is to prepare the adolescents entering the ideal age of marriage in the context of creating a quality family and controlling the population. In this case, Purbalingga Regency has a high level of early marriage. Thus, the PUP program is highly needed to realize the ideal age of marriage. Accordingly, the purpose of this study is to know the implementation of PUP in realizing the population control and developing family in Purbalingga Regency as well as revealing the factors that influence its implementation. This study employed juridical-empirical and qualitative approaches. The findings revealed the implementation of PUP program in Purbalingga Regency was realized in the form of KIE (Information and Education Communication). This was carried out by Dinsos Dalduk KB P3A in collaboration with PIK-R/M, Duta Genre, government agencies such as the health office, KUA, Ministry of Religious Affairs, Rural areas community development, and the participation of PLKB. However, this program was not fully implemented. Meanwhile, regarding the factors that influence its implementation, a supporting factors covered the partnership cooperation and support from religious leader and the community. The inhibiting factors, on the other hand, covered legal factors, law enforcement, means and facilities, personal factors, and social factors.Pendewasaan Usia Perkawinan (PUP) merupakan program BKKBN yang mengatur tentang pendewasaan batas usia perkawinan yaitu minimal 20 tahun bagi perempuan dan laki-laki minimal berusia 25 tahun, yang mana ketentuan tersebut berbeda dengan aturan batas usia perkawinan dalam Undang-Undang Perkawinan. Pentingnya program PUP adalah untuk mempersiapkan remaja memasuki usia perkawinan yang ideal dalam rangka membentuk keluarga berkualitas dan sarana sarana pengendalian penduduk. Kabupaten Purbalingga mempunyai tingkat perkawinan muda nya tinggi sehingga program PUP sangat dibutuhkan untuk mewujudkan usia perkawinan yang ideal. Penelitian ini bertujuan mengetahui implementasi Program PUP guna mewujudkan pengendalian penduduk dan pembangunan keluarga di Kabupaten Purbalingga dan faktor yang mempengaruhi implementasi dengan menggunakan metode penelitian yuridis empiris dan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa implementasi program PUP di Kabupaten Purbalingga dilakukan dalam bentuk KIE (Komunikasi Informasi dan Edukasi) oleh Dinsos Dalduk KB P3A bekerja sama dengan PIK-R/M, Duta Gendre, instansi pemerintah seperti Dinas Kesehatan, KUA, Kementerian Agama, pembinaan institusi masyarakat pedesaan, peran serta PLKB. Namun program PUP tersebut masih belum terlaksana secara menyeluruh. Adapun faktor –faktor yang mempengaruhi implementasi berupa faktor pendukung yaitu kerja sama kemitraan dan dukungan para tokoh agama dan masyarakat sedangkan faktor menghambatnya berupa faktor hukum, penegak hukum, sarana dan fasilitas, faktor personal, faktor sosial